Answer:
The answer is x = 1
Explanation:
You have the equation
-1=0 and below are the steps to complete
Step 1:
-1 = 0
Step 2: +1 =+1
Step 3:
= 1
Step 4:
=
![\sqrt[4]{1}](https://img.qammunity.org/2024/formulas/mathematics/college/ddr122evh8d2wu9zvjtvw8ieqxnfzjqm3q.png)
Step 5: x = 1
The First step shows to undo subtraction and add instead.
The Second Step shows 0 adding to 1.
The Third step shows how we have to square root it with 4 instead of 2.
The Fourth step shows the same thing to both sides.
The Fifth step leads the answer to be 1.
Then if we plug in 1 replacing x the equation will be true
I hope this was helpful!